Kajian Refleksi Teori Pengembangan Karakter Anak Melalui Pembelajaran Agama Perspektif Albert Bandura - Muali, Chusnul; Rohmatika, Putri Naily (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2019)
In the current reform era, character education has experienced a decline marked by increasing juvenile delinquency, corruption and moral deviations carried out by students and intellect to show character education has been eroded gradually. The role of school plays an important role in character development through religious learning. In the process, religious learning in schools should use two learning approaches, that is transfer of knowlage and transfer of value. Synchronized with the theory of Albert Bandura, the teacher as a model and students as a observers. As an observer, there are two processes in learning: that is 1) imitation processs, the learning process changes itself through certain stimuli, 2) modelling process, the process of changing his own behavior through observing the behavior of oth